FRI0490 Mortality and early severe infection in patients with anca-associated vasculitis. (12th June 2018) - Waki, D.; Nishimura, K.; Kadoba, K.; Mukoyama, H.; Saito, R.; Yokota, T.
Abstract : Background: The introduction of treatment regimens comprising of cyclophosphamide or rituximab combined with corticosteroids has brought about dramatic improvements in the prognosis of ANCA-associated vasculitis. 1 Severe infectious events, especially in the early phase of treatment, associated with risk of death have been reported in the past several studies. 2, 3 Objectives: We retrospectively investigated the association between mortality and early severe infection in patients with antineutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis (AAV), and we also attempted to identify the potential predictors for early severe infection. Methods: We recruited 182 consecutive hospitalised patients newly diagnosed with AAV at our hospital, from January 2000 to June 2017, in this retrospective cohort study. All cause mortality, relapse, and severe infections within six months after starting treatment (early severe infection) were analysed. Results: The mean age was 70 years at diagnosis, and the classification according to the Chapel Hill Conference definition were microscopic polyangiitis (MPA) in 82 patients (45.1%), granulomatosis with polyangiitis (GPA) in 36 patients (19.8%), eosinophilic granulomatosis with polyangiitis (EGPA) in 24 patients (13.2%), and renal-limited vasculitis in 32 patients (17.6%). 4 Median follow up was 158 weeks (range 0–182 w). Using Cox regression analysis, elderly onset (age ≥75 years) AAV (p = 0.027) and early severe infection (p ≤ 0.001) were independent predictors of all cause mortality (table 1). Early severe infection tended to increase among patients who received immunosuppressive therapy of a corticosteroid combined with cyclophosphamide or rituximab (conventional treatment), and this trend was significant in non-severe (BVAS <20) AAV patients (p = 0.030) (table 2). Treatment response rate (p=0.058) and relapse rate (p = 0.137) were not significant between the different treatment groups. Conclusions: Early severe infection is an independent predictor of death in patients with AAV, and conventional treatment has a potential risk of death due to severe infection. This study supports the current EULAR recommendation that several treatment strategies are recommended according to the disease severity of vasculitis. 5 AAV patients who receive conventional treatment should be carefully monitored to reduce the occurrence of severe infection, especially in early phase of treatment. References: [1] Little MA, et al. Ann Rheum Dis2010;69:1036–43. [2] Lai QY, et al. J Rheumatol2014;41(9):1849–55. [3] Solans-Laque R, et al. Medicine2017;96(8):e6083. [4] Janette JC, et al. Arthritis Rheum2013;65:1–11. [5] Yates M et al. Ann Rheum Dis 2016;75(9):1583–94. Disclosure of Interest: None declared